REVITALIZATION OF DIGITAL LEARNING: IS MOBIL MATEMATIKA WITH SMART APPS CREATOR EFFECTIVE FOR TEACHING NUMBERS? - Hadi Widodo; Jailani Jailani (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2025)
The insufficient understanding of number concepts at the elementary school level results in weak numeracy skills, impacting students' logical thinking and problem-solving abilities in higher education. This study aims to examine the effectiveness of an Android-based interactive multimedia, Mobil Matematika, in improving the achievement and learning motivation of third-grade elementary school students. Using the Research and Development (R&D) method based on the Multimedia for Learning model by Alessi & Trollip, the study involved third-grade students from SDN Dadaprejo 01 and 02, with 19 students for field trials and 18 students for product testing, as well as one teacher from SDN Pendem 01 and another from SDN Pendem 02 as expert practitioners. Data were collected through interviews, questionnaires, tests, and observations, then analyzed qualitatively and quantitatively. The results indicate that Mobil Matematika significantly enhances students' understanding of number concepts and learning motivation by integrating Constructivism Theory and Self-Determination Theory. The interactivity and feedback provided help students build their own understanding, highlighting the potential of interactive educational technology in improving learning outcomes. These findings emphasize the importance of instructional design that supports students' emotional and cognitive aspects, as well as the role of interactive technology in strengthening mathematics comprehension in elementary education.